Strategic responsiveness and adaptive organizations : new research frontiers in international strategic management - Andersen, Torben Juul; Torp, Simon; Linder, Stefan (Emerald studies in global strategic responsiveness, 2019)
The global business environment is becoming increasingly volatile and unpredictable, reflecting the consequences of operating in a dynamic and complex business environment in constant flux with the potential of extreme outcomes. As a consequence, corporate performance data generally displays very few high-performers and a fat tail of many underperforming firms. This business context means that contemporary managers need to be equipped to deal effectively with implied uncertainty, abrupt events, and extreme outcome effects.This volume presents a number of promising ideas about how to deal with the strategic challenges of global business turbulence, as presented at the 2018 EURAM Conference held in Reykjavik, Iceland. There is a need for effective adaptive strategies to survive and prosper in the unpredictable contexts of corporate activities. The various contributions are grounded in prior strategy research but adopt multiple methodological approaches to engage diverse relevant knowledge that can advance this increasingly important field of study.The book presents new perspectives in the study of responsive adaptive processes in organizational settings that has high relevance for social science researchers with interests in these issues. Intelligent and curious managers and management students can likewise gain access to new ideas that may inspire their current thinking on effective organizational practices.